2012
DOI: 10.1089/end.2011.0193
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Anatrophic Nephrolithotomy: Developments of the Technique in the Era of Minimally Invasive Surgery

Abstract: Laparoscopic surgery is feasible when anatrophic nephrolithotomy is indicated. This technique minimizes the barriers of an open flank incision, while achieving excellent stone-free rates. This minimally invasive technique should be considered for complex stones that would necessitate multiple renal access tracks and secondary procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 22 publications
0
26
1
Order By: Relevance
“…24 We used two rows of running sutures for closure of the renal parenchyma, others have shown that one layer closure, in favor of WIT, would be sufficient in this setting. [6][7][8] Some limitations of this study, however, deserve mention. Our sample size was admittedly small.…”
Section: Aminsharifi Et Almentioning
confidence: 85%
See 1 more Smart Citation
“…24 We used two rows of running sutures for closure of the renal parenchyma, others have shown that one layer closure, in favor of WIT, would be sufficient in this setting. [6][7][8] Some limitations of this study, however, deserve mention. Our sample size was admittedly small.…”
Section: Aminsharifi Et Almentioning
confidence: 85%
“…1,2,5 Performing AN for complete staghorn renal stone in a minimally invasive milieu of laparoscopy was recently introduced with acceptable early postoperative outcomes in small sample sizes. [6][7][8] Despite promising early postoperative outcome of laparoscopic anatrophic nephrolithotomy (LAN), little is known about the impact of this procedure on the ultimate renal function during an intermediate or long-term follow-up period. This could be an important concern, because during LAN, the kidney is exposed to warm ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…63 A minimally invasive alternative to open ANL is laparoscopic and robotic ANL, which have recently been described. [54][55][56][57] In preparation for surgery, a noncontrast CT scan is obtained to delineate the anatomy and guide the surgical approach. A renogram should be obtained if there is concern for a poorly functioning renal unit, and nephrectomy considered if poor function is confirmed and the contralateral kidney is normal.…”
Section: Surgical Treatment Options Infection Stonesmentioning
confidence: 99%
“…53 Of the small series publishing their outcomes of robotic and laparoscopic ANL, reported complications include gross hematuria requiring continuous bladder irrigation, blood transfusion, splenic injury necessitating splenectomy, and vascular fistula. 54,56,85 Obstructive Pyelonephritis Patients with obstructive pyelonephritis are at risk to develop urosepsis and its sequelae, including acute kidney injury and death. Mortality rates for patients with obstructive pyelonephritis and sepsis are reported at 9% for those undergoing surgical decompression and 19% for those without decompression.…”
Section: Treatment Resistance/complications Infection Stonesmentioning
confidence: 99%
“…Despite encouraging stonefree rates, the authors recommended that consideration of this pro cedure should be limited to expert laparo scopic surgeons. Giedelman and colleagues 45 published results from eight patients who underwent laparoscopic anatro phic nephro lithotomy, reporting mixed success. Although no cases required conversion to an open pro cedure, three patients were not stone free 15 days after the procedure and one patient developed a vascular fistula requiring embolization.…”
Section: Incision Sitementioning
confidence: 99%